DFT study of the adsorption of glycerol on K2O (1 1 0) for biodiesel production - Juan, Julián (2025)
A Density Functional Theory based study was performed to understand glycerol adsorption on the K2O (1 1 0)surface. The (1 1 0) surface was theoretically found to have the lowest surface energy and therefore is the mostprobable one to be formed. Glycerol was adsorbed in three different orientations, finding favorable highadsorption energies in all cases. On the adsorption sites, geometry alterations in the surface can be seen, with themovement of potassium atoms to bond oxygen atoms of glycerol. Electronic structure calculations were conducted, showing the density of states for the (1 1 0) clean surface and for the adsorbed systems. From theseresults, a band gap reduction is appreciated, with a behavior similar to a “p” type semiconductor in both pure andadsorbed scenarios. Bond order studies were performed, showing that potassium atoms have lowered their bondstrength due to their higher distancing from the surface to a nearby glycerol. Bader charge and charge densitydifference analysis showed a charge transfer from the surface to the glycerol molecule in the adsorbed systems.Therefore, this study gives innovative information of glycerol adsorption on this surface that is a strong candidateas catalyst for biodiesel production, which is a guide for future theoretical and experimental works.